Activated Hair Follicle Stem Cells and Wnt/β-catenin Signaling Involve in Pathnogenesis of Sebaceous Neoplasms - Qiu, Weiming (Ivyspring International Publisher, 2014)
Sebaceous glands (SGs) undergo cyclic renewal independent of hair follicle stem cells (HFSCs) activation while HFSCs have the potential to differentiate into sebaceous gland cells, hair follicle and epidermal keratinocytes. Abnormalities of sebaceous gland progenitor cells contribute to the development of sebaceous neoplasms, but little is known about the role of HFSCs during sebaceous neoplasm development. Here, using dimethylbenzanthracene (DMBA) plus 12-o-tetradecanoyl phorbol-13-acetate (TPA) treatment developing sebaceous neoplasms (SNs) were identified with H&E and Oil red O staining. And then the molecular expression and activation of HFSCs and was characterized by immunostaining. Wnt10b/β-catenin signaling molecular which is important for activation of HFSCs were detected by immunostaining. We found hair follicle and epidermal cell markers were expressed in sebaceous neoplasms. Furthermore, SOX-9 and CD34-positive HFSCs were located in the basal layer of sebaceous lobules within the sebaceous neoplasms. Many appear to be in an active state. Finally, Wnt10b/β-catenin signaling was activated within the basal cells of sebaceous lobules in the sebaceous neoplasms. Collectively, our findings suggest that the abnormal activation of both HFSCs and Wnt10b/β-catenin signaling involves in the development of sebaceous neoplasms.